1998
DOI: 10.1042/bj3330291
|View full text |Cite
|
Sign up to set email alerts
|

The cellular response to oxidative stress: influences of mitogen-activated protein kinase signalling pathways on cell survival

Abstract: The mammalian response to stress is complex, often involving multiple signalling pathways that act in concert to influence cell fate. To examine potential interactions between the signalling cascades, we have focused on the effects of a model oxidant stress in a single cell type through an examination of the relative influences of mitogen-activated protein kinases (MAPKs) as well as two proposed apoptosis regulators, nuclear factor kappaB (NF-kappaB) and Bcl-2, in determining cell survival. Treatment of HeLa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
479
3
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 692 publications
(534 citation statements)
references
References 44 publications
42
479
3
5
Order By: Relevance
“…Our results suggest that STC1 functions in a negative feedback loop to regulate MEK and ERK1/2. The higher levels of activated MEK and ERK1/2 in STC1À/À MEFs were associated with resistance to oxidative stress, in agreement with the observation that ERK1/2 has a mitogenic or prosurvival function (Wang et al, 1998). Therefore, the MEK-ERK1/2-STC1 negative feedback loop downregulates the ERK1/2 prosurvival signaling pathway and decreases survival of MEFs in response to oxidative stress.…”
Section: Regulation Of Oxidative Stress Response By Stc1supporting
confidence: 86%
See 1 more Smart Citation
“…Our results suggest that STC1 functions in a negative feedback loop to regulate MEK and ERK1/2. The higher levels of activated MEK and ERK1/2 in STC1À/À MEFs were associated with resistance to oxidative stress, in agreement with the observation that ERK1/2 has a mitogenic or prosurvival function (Wang et al, 1998). Therefore, the MEK-ERK1/2-STC1 negative feedback loop downregulates the ERK1/2 prosurvival signaling pathway and decreases survival of MEFs in response to oxidative stress.…”
Section: Regulation Of Oxidative Stress Response By Stc1supporting
confidence: 86%
“…The ERK family of proteins play central roles in regulating the survival of cells in response to oxidative stress (Wang et al, 1998), so we examined whether altered ERK1/2 signaling might account for the resistance of STC1À/À MEFs to oxidative stress. Western blot analysis for phosphorylated ERK1/2 revealed that STC1À/À MEFs had higher levels of activated ERK1/2 than STC1 ĂŸ / ĂŸ MEFs (Figure 4a), but total ERK1/2 protein levels in STC1 ĂŸ / ĂŸ and STC1À/À MEFs were similar (Figure 4a).…”
Section: Regulation Of Oxidative Stress Response By Stc1 a Nguyen Et Almentioning
confidence: 99%
“…Growth factor receptors have been shown to undergo enhanced phosphorylation in response to oxidative insults like hydrogen peroxide or UV-radiation initiating ERK1/2 activation [115,116,210]. This is consistent with demonstrations of the mitogenic effects of low concentrations of hydrogen peroxide [23].…”
Section: Mapk Signaling Under Oxidative Stresssupporting
confidence: 74%
“…Results illustrated that, despite high expression, MEK1/2 and ERK1/2 proteins were mainly unphosphorylated in untreated NCCIT cells (Figure 3). However, phosphorylation of MEK1/2 and ERK1/2 proteins began to increase at 6 h and was at its highest at 12 h after CDDP treatment, a course which has been observed in growth factor-or oxidantmediated MEK -ERK activation in many cell types (Jimenez et al, 1997;Wang et al, 1998). Interestingly, MEK1 and ERK2 seem to be more strongly phosphorylated than MEK2 and ERK1.…”
Section: Cddp-induced Activation Of the Mek -Erk Signalling Pathwaymentioning
confidence: 87%